2017
DOI: 10.1007/s10072-017-3080-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis and environmental risk factors: a case-control study in Iran

Abstract: Studies have shown an increase in the incidence of MS in Iran. The aim of our study was to evaluate the relationship between environmental exposure and MS in Iran. This case-control study was conducted on 660 MS patients and 421 controls. Many environmental factors are compared between the two groups. Our findings demonstrated that prematurity ([OR = 4.99 (95% CI 1.34-18.68), P = 0.017]), history of measles and mumps ([OR = 1.60 (95% CI 1.05-2.45), P = 0.029; OR = 1.85 (95% CI 1.22-2.78), P = 0.003, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 44 publications
3
42
1
Order By: Relevance
“…Two studies conducted in Saudi Arabia found an association between MS and measles, 45 , 46 which is consistent with a case-control study conducted in 2017 in Iran that identified an association between a history of measles and MS. 55 , 56 This is also consistent with a report that a history of measles during childhood increases the MS risk. 57 The association between MS and measles infection has been studied for many years, and this association has been postulated as a host response to viral infection, which may cause the demyelinating and inflammatory lesions in MS. 58 A serological study in Kuwait found that EBV increased the MS risk and the authors identified a strong association between EBV and MS. 48 The findings of that study are consistent with a meta-analysis reporting that a history of infectious mononucleosis more than doubles the risk of MS. 59 It is currently unclear whether EBV is independently associated with MS or whether some other factors predispose an individual to both EBV infection and MS. EBV affects people of all ages, and, after causing an asymptomatic primary infection early in childhood, the virus exists in a latent form in B cells, from which it can later progress to infectious mononucleosis.…”
Section: Discussionsupporting
confidence: 91%
“…Two studies conducted in Saudi Arabia found an association between MS and measles, 45 , 46 which is consistent with a case-control study conducted in 2017 in Iran that identified an association between a history of measles and MS. 55 , 56 This is also consistent with a report that a history of measles during childhood increases the MS risk. 57 The association between MS and measles infection has been studied for many years, and this association has been postulated as a host response to viral infection, which may cause the demyelinating and inflammatory lesions in MS. 58 A serological study in Kuwait found that EBV increased the MS risk and the authors identified a strong association between EBV and MS. 48 The findings of that study are consistent with a meta-analysis reporting that a history of infectious mononucleosis more than doubles the risk of MS. 59 It is currently unclear whether EBV is independently associated with MS or whether some other factors predispose an individual to both EBV infection and MS. EBV affects people of all ages, and, after causing an asymptomatic primary infection early in childhood, the virus exists in a latent form in B cells, from which it can later progress to infectious mononucleosis.…”
Section: Discussionsupporting
confidence: 91%
“…Observational studies suggest higher MS risk with lower sun exposure in childhood, adolescence, adulthood, and over the whole life . The findings are relatively, but not completely, consistent, despite the wide range of ways of measuring sun exposure.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 86%
“…Studies of cesarean section delivery and having been breastfed, both of which have profound effects on the microbiome, have yielded mixed results. Both deserve further study as these are modifiable factors.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%
“…An EnvIMS-based study concluded that vigorous physical activity may decrease the risk of development of MS, but our study found an insignificant association between vigorous physical activity and the development of MS. 32 Another study investigating lifestyle risk factors also found an insignificant association between physical activity and MS. 33 However, a large prospective study using a validated measure of physical activity found weak evidence that higher physical activity may decrease the risk of development of MS. 34 Our study found that a history of measles infection may decrease the risk of MS. Another study found a significant association between measles infection and the development of MS. 35 In a case-control study conducted in 2017 to examine environmental risk factors, a significant association was found between a history of measles or mumps and MS (OR=1.60, 95% CI 1.05-2.45, p =0.029). 36 Another study found that a history of infection during childhood (such as measles) increased the risk of MS. 37 The association between MS and measles infection has been studied for a long time, the association postulated as host response to virus infection because virus may cause demyelinating and inflammatory lesions of MS. 38 …”
Section: Discussionmentioning
confidence: 99%